2002
DOI: 10.1007/s003800200030
|View full text |Cite
|
Sign up to set email alerts
|

Structural differences in the cytoarchitecture and intercalated discs between the working myocardium and conduction system in the human heart

Abstract: Working and specialized cardiac myocytes and their intercalated discs in adult human hearts without history of cardiac disease were examined by scanning electron microscopy. The NaOH/ultrasonication treatment of cardiac tissues resulted in the digestion of connective tissue and separation of intercellular junctions. Auricular and ventricular working cardiac myocytes were quasi-cylindrical in shape, bifurcated, and connected end-to-end at the intercalated discs. The intercalated discs in the working cardiac myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 18 publications
3
19
0
Order By: Relevance
“…Glutaraldehyde pre‐fixed specimens were washed in 0.1 mmol natrium cacodylate buffer (pH 7.4) and immersed in 6 N NaOH for 10–15 min. at 60°C to digest collagen fibres and basement membrane as previously described [44]. The specimens were washed thoroughly in PBS and post‐fixed in 1% osmium tetroxide for 1 hr.…”
Section: Methodsmentioning
confidence: 99%
“…Glutaraldehyde pre‐fixed specimens were washed in 0.1 mmol natrium cacodylate buffer (pH 7.4) and immersed in 6 N NaOH for 10–15 min. at 60°C to digest collagen fibres and basement membrane as previously described [44]. The specimens were washed thoroughly in PBS and post‐fixed in 1% osmium tetroxide for 1 hr.…”
Section: Methodsmentioning
confidence: 99%
“…18,19) Recently the intercalated disks in the mammalian heart were visualized three-demensionally by utilizing scanning electron microscopic techniques combined with the NaOH/ultrasonication method. [20][21][22] The intercalated disks of myocytes in the crista terminalis and surrounding the fossa ovalis were apparently different in three-dimensional architecture from those of atrial myocytes. 21) Thus, in spite of the numerous morphological studies on the working myocardium and the cardiac conduction system, relatively little attention has been paid to the BB for many years.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] The intercalated disks of myocytes in the crista terminalis and surrounding the fossa ovalis were apparently different in three-dimensional architecture from those of atrial myocytes. 21) Thus, in spite of the numerous morphological studies on the working myocardium and the cardiac conduction system, relatively little attention has been paid to the BB for many years. 23) Recently, it has been suggested that Bachmann's bundle pacing is effective for the prevention of atrial fibrillation (AF), 24,25) and many clinical and experimental data about AF and BB have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Each gap junction channel consists of subunit proteins called connexin (Cx) (Kumar and Gilula, 1996). The number, size, and distribution of the gap junctions in the heart play an important role in determining the conduction properties of the different cardiac tissues (Vozzi et al, 1999;Miyamoto et al, 2002). In the mammalian heart, gap junctions are composed of Cx40, Cx43, Cx45 and Cx37.…”
Section: Introductionmentioning
confidence: 99%